Analysis and Comparison of Length Measurement Scenarios from the Solar System to the Galaxy - Xue, Yuhan (Transactions on Computer Science and Intelligent Systems Research, 2024)
As a matter of fact, astronomical research depends heavily on distance measurement between the Earth and celestial objects, so it’s crucial to employ effective method along with advanced instrument for distance measurement. This study talks about the three most commonly used strategies to measure distance in space. Stellar parallax, based on trigonometry and the concept of stereoscopic vision, is the most conventional method to measure the distances within the Milky Way. Cepheid Variables, with their consistent period-luminosity relationship, become useful when measuring distances to nearby galaxies. Type 1a supernova that worked as standard candles can be used to measure distance that parallax and Cepheid variables cannot achieve. According to the analysis, these three methods each plays an important role in the cosmic distance ladder and excels in different distance ranges. Even though more accurate techniques are still needed for a more propound exploration of the universe, these methods become a foundation for future advancement in astronomical distance measurement.